Atypical Parathyroid Adenoma Complicated with Protracted Hungry Bone Syndrome after Surgery: A Case Report and Literature Review - Óscar Alfredo Juárez-León; Miguel Ángel Gómez-Sámano; Daniel Cuevas-Ramos; Paloma Almeda-Valdés; Manuel Alejandro López-Flores A La Torre; Alfredo Adolfo Reza-Albarrán; Francisco Javier Gómez-Pérez (Case Reports in Endocrinology)
Hungry Bone Syndrome refers to the severe and prolonged hypocalcemia and hypophosphatemia, following parathyroidectomy in patients with hyperparathyroidism. We present the case of an eighteen-year-old woman with a four-year history of hyporexia, polydipsia, weight loss, growth retardation, and poor academic performance. The diagnostic work-up demonstrated primary hyperparathyroidism with hypercalcemia of 13.36 mg/dL, a PTH level of 2551 pg/mL, bone brown tumors, and microcalcifications within pancreas and kidneys. Neck ultrasonography revealed a parathyroid adenoma of 33 × 14 × 14 mm, also identified on 99Tc-sestamibi scan. Bone densitometry showed decreased Z-Score values (total lumbar Z-Score of −4.2). A right hemithyroidectomy and right lower parathyroidectomy were performed. Pathological examination showed an atypical parathyroid adenoma, of 3.8 g of weight and 2.8 cm in diameter. After surgery she developed hypocalcemia with tetany and QTc interval prolongation. The patient required 3 months of oral and intravenous calcium supplementation due to Hungry Bone Syndrome (HBS). After 42 months, she is still under oral calcium. Usually HBS lasts less than 12 months. Therefore we propose the term “Protracted HBS” in patients with particularly long recovery of 1 year. We present a literature review of the diagnosis, pathophysiology, and treatment of HBS.